2002
DOI: 10.1080/mmy.40.3.259.262
|View full text |Cite
|
Sign up to set email alerts
|

fos-1, a putative histidine kinase as a virulence factor for systemic aspergillosis

Abstract: In fungi, two-component histidine kinases have various functions including regulation of osmosensitivity, and of cell-wall assembly. Furthermore, one of these proteins, cos-1, has been shown to be important for virulence of Candida albicans. Recently, a putative histidine kinase, fos-1, has been isolated and partially characterized from Aspergillus fumigatus. Here we compare the virulence of a fos-1 deletion strain with that of the parental wild-type strain in a murine model of systemic aspergillosis. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Two-component signal transduction pathways present attractive targets for antifungal drug discovery because they exist in prokaryotes, plants, and lower eukaryotes but not in mammalian cells. Furthermore, while the genes encoding two-component system proteins are frequently not essential for viability, multiple studies have demonstrated the importance of two-component signal proteins for virulence in fungal pathogens, including A. fumigatus [10], C. albicans [1113], C. neoformans [14], B. dermatitidis , and H. capsulatum [15] (Table 1). …”
Section: Two-component Signal Transduction Pathways In Fungal Pathogementioning
confidence: 99%
“…Two-component signal transduction pathways present attractive targets for antifungal drug discovery because they exist in prokaryotes, plants, and lower eukaryotes but not in mammalian cells. Furthermore, while the genes encoding two-component system proteins are frequently not essential for viability, multiple studies have demonstrated the importance of two-component signal proteins for virulence in fungal pathogens, including A. fumigatus [10], C. albicans [1113], C. neoformans [14], B. dermatitidis , and H. capsulatum [15] (Table 1). …”
Section: Two-component Signal Transduction Pathways In Fungal Pathogementioning
confidence: 99%
“…They were usually tested in virulence studies that focused on fungal factors like proteins of the cell wall integrity, elastase, and other miscellaneous proteases (Kothary et al, 1984; Kolattukudy et al, 1993; Frosco et al, 1994), catalases (Paris et al, 2003), phospholipase, toxins (Paris et al, 1993; Bok et al, 2006; Cramer et al, 2006; Sugui et al, 2007a,b; Gravelat et al, 2008; Ben-Ami et al, 2009; Wang et al, 2014), adhesins, restrictocins (Smith et al, 1993), conidial pigments like melanin (Jahn et al, 1997; Langfelder et al, 1998), histidine kinase (Bartroli et al, 1998; Clemons et al, 2002; Du et al, 2002), calcineurine (Steinbach et al, 2006; Juvvadi et al, 2013), alkaline protease (Monod et al, 1993; Tang et al, 1993; Jaton-Ogay et al, 1994; Smith et al, 1994), and chitin synthase (Mellado et al, 1996; Aufauvre-Brown et al, 1997). …”
Section: Resultsmentioning
confidence: 99%
“…It was evidenced a dose-dependent correlation regarding the number of conidia in the inoculum with the severity of infection, regardless of the rodent model and the A. fumigatus strain (Dixon et al, 1989; Hector et al, 1990; Chiller et al, 2002; Clemons et al, 2000a, 2002), but our bibliographic analysis highlighted very large variations, ranging for instance from 1.0 × 10 2 (Waldorf et al, 1984) to 1.0 × 10 9 (Graybill et al, 1998) for mice infected by intranasal route. In addition, culture conditions and pre-infection technical steps are also great challenges for harmonization.…”
Section: Discussionmentioning
confidence: 99%
“…The A. fumigatus genome contains~15 HKs (Nierman et al, 2005), of which only three (Fos1, TcsB and NikA/TcsC) have thus far been functionally characterized (Clemons et al, 2002;Du et al, 2006;Hagiwara et al, 2013). While TcsB has been reported to be dispensable for most cellular functions (Du et al, 2006), Fos1 has been shown to regulate cell wall assembly and virulence (Clemons et al, 2002).…”
Section: Histidine Kinases (Hk)mentioning
confidence: 98%
“…While TcsB has been reported to be dispensable for most cellular functions (Du et al, 2006), Fos1 has been shown to regulate cell wall assembly and virulence (Clemons et al, 2002). More recently, NikA/TcsC was reported to be involved in conidia and hyphae production, resistance to osmotic stress, and resistance to cell wall perturbing reagents and fungicides (Hagiwara et al, 2013).…”
Section: Histidine Kinases (Hk)mentioning
confidence: 98%